2011
DOI: 10.1037/a0025069
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Intuition: A Process and Outcome Framework

Abstract: In recent years, the topic of intuition has become an important focus of attention in psychology. It is often assumed to be a unitary construct; however, recent research suggests that intuition is multifaceted. This article disaggregates intuition by discriminating between domain-general mechanisms and domainspecific processes of intuiting and primary types of intuition and secondary types of intuition. The theoretical relationships between and within processes and types are examined and analyzed at behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 117 publications
1
74
0
Order By: Relevance
“…Given that intuition and analysis are domain‐general processes (Gore and Sadler‐Smith ), we conclude that the explicit integration of paradox theory with dual‐processing theory in its various forms has potential to shed light on a variety of decision‐making and related phenomena across a wide range of management sub‐fields. The use of paradox theory in trying to understand intuition and analysis moves debates forward from simplistic questions such as ‘is it best to use intuition or analysis?’ or ‘under what conditions do we chose intuition or analysis’ (e.g.…”
Section: Psychological and Psychometric Issues In The Relationship Bementioning
confidence: 96%
“…Given that intuition and analysis are domain‐general processes (Gore and Sadler‐Smith ), we conclude that the explicit integration of paradox theory with dual‐processing theory in its various forms has potential to shed light on a variety of decision‐making and related phenomena across a wide range of management sub‐fields. The use of paradox theory in trying to understand intuition and analysis moves debates forward from simplistic questions such as ‘is it best to use intuition or analysis?’ or ‘under what conditions do we chose intuition or analysis’ (e.g.…”
Section: Psychological and Psychometric Issues In The Relationship Bementioning
confidence: 96%
“…In contrast, intuition produces only an unsubstantiated “feeling” supporting an alternative or course of action (Dane and Pratt, ). It produces a sense of “what direction,” but does not include “why.” Intuition arrives in the conscious mind before the insight, and is, therefore, a precursor to insight (Gore and Sadler‐Smith, ; Wallas, ). Becoming fully conscious of a complete insight can be slow and sometimes answers never arrive to our conscious awareness as a complete insight (Hodgkinson, Sadler‐Smith, Burke, Claxton, and Sparrow, ; Sadler‐Smith and Shefy, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This clinician and patient relationship has been described as intuitive practice (English 1993;Gore & Sadler-Smith 2011;Smith et al 2004) and is well documented in nursing literature. A qualitative study that explored the opinions and beliefs of nurses' intuition, suggested that it is an interaction of attributes including: expertise; knowledge; personality; and the environment (McCutcheon and Pincombe 2001).…”
Section: Cognition and Emotional Markersmentioning
confidence: 95%